2017
DOI: 10.1177/1535370217742600
|View full text |Cite
|
Sign up to set email alerts
|

Increased serum levels of mBDNF in women with minimal and mild endometriosis have no predictive power for the disease

Abstract: The objective of our pilot clinical, prospective study was to determine the serum levels of mature brain-derived neurotrophic factor, in of women with endometriosis and controls and explore whether mature brain-derived neurotrophic factor is a potential biomarker for the disease. The patients were selected from the Endometriosis Marker Austria prospective cohort study conducted at the tertiary referral certified Endometriosis Center of the Medical University of Vienna. All women underwent laparoscopic surgery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…Many studies have examined candidate biomarkers in accessible body fluids (primarily blood) based on current knowledge of the pathogenesis of endometriosis, as has been well summarized by previous reviews (Figure 1(b)). 12,31,32 We used this strategy to test the applicability of the differences in the levels of secretion of the adhesion molecules VCAM-1 and ICAM-1, 11 pain regulatory protein BDNF, 33 and the regulators of inflammation (soluble CD40 Ligand and CXCL1) 34 in the serum of women with and without endometriosis. However, only one of the three studies validated our initial hypothesis.…”
Section: Hypothesis-driven Biomarker Discoverymentioning
confidence: 99%
“…Many studies have examined candidate biomarkers in accessible body fluids (primarily blood) based on current knowledge of the pathogenesis of endometriosis, as has been well summarized by previous reviews (Figure 1(b)). 12,31,32 We used this strategy to test the applicability of the differences in the levels of secretion of the adhesion molecules VCAM-1 and ICAM-1, 11 pain regulatory protein BDNF, 33 and the regulators of inflammation (soluble CD40 Ligand and CXCL1) 34 in the serum of women with and without endometriosis. However, only one of the three studies validated our initial hypothesis.…”
Section: Hypothesis-driven Biomarker Discoverymentioning
confidence: 99%
“…Data obtained from clinical samples showing that plasma concentrations of BDNF were significantly higher in women with endometriosis (Stages I and II) (Wessels et al , 2016; Rocha et al , 2017; Perricos et al , 2018) may indicate the potential use of BDNF in diagnosing this chronic disease in its early stage. The participation of NGF signaling in the development of ovarian cancer and the findings that NGF and TrkA are highly expressed in women with EOC suggest that NGF may be applied as a biomarker for ovarian cancer.…”
Section: Clinical Applications and Therapeutic Potentialmentioning
confidence: 99%
“…Furthermore, the estrogen-induced upregulation of BDNF and TrkB that enhances the proliferation of endometrial cells in uterine tissue has been proposed to explain the pathogenesis of estrogen-dependent diseases, including endometriosis (Wessels et al , 2015; Dong et al , 2017). Indeed, recent clinical studies have reported that plasma concentrations of BDNF were significantly higher in women with endometriosis, especially in Stages I and II disease, indicating that BDNF is a potential clinical marker for this painful disorder during its early stage (Wessels et al , 2016; Rocha et al , 2017; Perricos et al , 2018). Targeted genetic association analysis of a case-control study including 425 patients with endometriosis revealed the presence of a BDNF SNP that was linked to an increased severity of endometriosis (Stage III and Stage IV) (Zhang et al , 2012).…”
Section: Roles For Nts In Ovarian Pathology and Diseasesmentioning
confidence: 99%
“…Indeed, women with endometriosis have elevated circulating BDNF concentrations compared to women without disease 19 21 , which correlated with pelvic pain 21 , and decreased after surgical removal of lesions 19 . However the clinical value of BDNF as a marker of endometriosis has also been challenged 21 , 22 . While some studies find BDNF to be a useful clinical marker of endometriosis or certain endometriotic lesion types 19 21 , others find the difference in BDNF between women with and without endometriosis is not predictive of disease 21 , 22 .…”
Section: Introductionmentioning
confidence: 99%
“…However the clinical value of BDNF as a marker of endometriosis has also been challenged 21 , 22 . While some studies find BDNF to be a useful clinical marker of endometriosis or certain endometriotic lesion types 19 21 , others find the difference in BDNF between women with and without endometriosis is not predictive of disease 21 , 22 . The reasons for variable and divergent findings between studies is difficult to resolve, but could include the fact that some studies quantified BDNF in plasma whilst others used serum, or that different ELISA kits were used for quantification.…”
Section: Introductionmentioning
confidence: 99%